2017
DOI: 10.3329/jesnr.v10i1.34690
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Proximate Composition, Quality and Heavy Metal Concentration of two Sun-Dried Marine Fish (Sun-Dried Silver Pomfret and Sun-Dried Perch) of Cox’s Bazar District of Bangladesh

Abstract: This research was conducted on the proximate composition, quality aspect and heavy metal concentration of sun-dried Silver Pomfret (Stromateus cinereus) and sun-dried Perch (Lates calcarifer) which were collected from local market of Cox"s Bazar town. These sundried marine fishes were collected from the stock after first drying procedure. Organoleptically most of these sun-dried fishes were in "excellent" grade some were in "Good" grade. Crude Protein, Lipid, Moisture, Ash, TVB-N and TMA-N content (%) of sun-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
1
5
1
Order By: Relevance
“…However, the findings of this study showed that the average protein level obtained from dried fishes were very close with the previous studies. The present study agreed with Hossain et al (2017) lipid content (%) of sun-dried Silver Pomfret and Perch was 7.75±0.20 and 5.03±0.55%, respectively. Hoque et al (2018) found that the lipid contents on wet weight basis for the products 12.9% to 18.80% respectively.…”
Section: Proximate Analysis Of Dried Fish Samplesupporting
confidence: 91%
See 3 more Smart Citations
“…However, the findings of this study showed that the average protein level obtained from dried fishes were very close with the previous studies. The present study agreed with Hossain et al (2017) lipid content (%) of sun-dried Silver Pomfret and Perch was 7.75±0.20 and 5.03±0.55%, respectively. Hoque et al (2018) found that the lipid contents on wet weight basis for the products 12.9% to 18.80% respectively.…”
Section: Proximate Analysis Of Dried Fish Samplesupporting
confidence: 91%
“…The finding of Hoque et al (2018) observed that the moisture content of improved traditional dryer dried fish products ranged from 16.71% to 21.1%. The study of Hossain et al (2017) found crude protein content (%) of Silver Pomfret and Perch at 32.25±1.50, and 40.31±2.13, respectively which was less similar to present findings. In other study similar findings of protein contents on wet weight ranged from 55.2% to 60.16% in case of improved traditional dryer dried Silver pomfret, Bombay duck and Ribbon fish observed by (Hoque et al 2018).…”
Section: Proximate Analysis Of Dried Fish Samplecontrasting
confidence: 63%
See 2 more Smart Citations
“…However, in previous studies, the acceptablity limit for TVB-N was considered to be 100 mg/100g (Connell, 1980), which is much higher than the recent classifications. Accordingly, Hossain et al (2017) found that TMA-N and TVB-N values of open-sun dried Silver Pomfret and open-sun dried Perch fish were within the human acceptablity levels. The TMA-N and TVB-N values for Perch dried-fish were 8.21±0.12 and 46.97±1.00 mg/100g, respectively and for Silver Pomfret, the values were 9.41±0.37 and 85.68±1.60 mg/100g, respectively.…”
Section: Health Aspects Of Solar-dried Fishmentioning
confidence: 92%